A capacitive pressure-sensitive chip with linkage film. (December 2021) - Chuai, Rongyan; Zhang, Bing; Yang, Yuxin; Jiang, Guimin; Zhang, He; Li, Xin
Abstract: In order to enhance the performance of capacitive pressure sensors, a novel pressure-sensitive chip with linkage film is designed. In this construct, its top electrode plate adopts a composite three-layer membrane. A finite element method is used to analyze the response characteristics of the sensitive construct, and the simulated results show that significant improvements in the linear operation range and the linearity can be achieved. A sample chip with a scale range of 0–100 kPa is trial-produced by using SOI wafers combined with the silicon-silicon fusion bonding process, and the process flow is presented. The tested results indicate that the sensitivity of the sample chip reaches 0.057 pF/kPa in the pressure range of 20–64 kPa, and its non-linearity is about 3.1%FS.